اسباب ورود الحديث وأثرها على المباحث الأصولية دراسة حديثية - أمين, صلاح سعيد; القرداغي, إبراهيم فتاح قادر (Sulaimani Journal for Humanities, 2021)
Hadith : A Hadith refers to all that is narrated from the Prophet, his acts, his sayings, and whatever he tacitly approved, in addition to all the reports which describe his physical attributes and character. The foundations of the reasons for the emergence of Hadith go back to the questions of the Companions, God bless them in general, who lived in the early stages of Islam.. The reasons for the emergence of Hadith have a great impact on fundamental investigations: specifying the general, determining the whole, limiting the absolute, identifying the abrogator and the abrogated, identifying the reasons of judgment, clarifying problematic statements in the texts of Hadith.